AC002454.1 and CDK6 synergistically promote endometrial cell migration and invasion in endometriosis. Issue 6 (June 2019) - Liu, Jing; Wang, Yang; Chen, Peng; Ma, Yue; Wang, Shuo; Tian, Ye; Wang, Anna; Wang, Danbo
Abstract : Previous lncRNA microarray screening found that the AC002454.1 gene was highly expressed in endometriosis (EMS), and these expression levels were highly correlated with cyclin-dependent kinase-6 (CDK6). This study investigated the expression level and correlation between AC002454.1 and CDK6 in endometrium tissues and the influence of these changes in expression upon the biological behavior of eutopic endometrial cells. We confirmed AC002454.1 and CDK6 mRNA and protein were highly expressed in ectopic and eutopic endometrial tissue from patients with EMS and were clearly correlated. In vitro, both AC002454.1 and CDK6 positively regulated the proliferation, migration and invasion ability of eutopic endometrial cells and could promote the transformation of cells from G0/G1 phase to S phase. AC002454.1 and CDK6 may have synergistic effects, thereby affecting the biological behavior of endometrial cells, and thus promote the progression of EMS.